2022
DOI: 10.1021/acs.jmedchem.2c00551
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Leucine-Rich Repeat Kinase 2 In Vivo with 18F-Labeled Positron Emission Tomography Ligand

Abstract: Leucine-rich repeat kinase 2 (LRRK2) has been demonstrated to be closely involved in the pathogenesis of Parkinson's disease (PD), and pharmacological blockade of LRRK2 represents a new opportunity for therapeutical treatment of PD and other related neurodegenerative conditions. The development of an LRRK2-specific positron emission tomography (PET) ligand would enable a target occupancy study in vivo and greatly facilitate LRRK2 drug discovery and clinical translation as well as provide a molecular imaging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 62 publications
(126 reference statements)
2
28
0
Order By: Relevance
“…23 An in vitro autoradiography study of [ 18 F]PF-06455943 in a baboon brain tissue showed high binding in the caudate, hippocampus, thalamus, and cortex, while lower binding was observed in the hypothalamus. 19 Our in vivo imaging results agree with those findings in vitro.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…23 An in vitro autoradiography study of [ 18 F]PF-06455943 in a baboon brain tissue showed high binding in the caudate, hippocampus, thalamus, and cortex, while lower binding was observed in the hypothalamus. 19 Our in vivo imaging results agree with those findings in vitro.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Favorable in vivo specific binding was also demonstrated by a LC-MS/MS study in mice. 19 In this study, dynamic PET scans were performed in macaques (n = 2) using [ 18 F]PF-06455943 with arterial blood sampling to compare kinetic modeling approaches to determine the optimal kinetic models describing the performance of the radiotracer. 22 As demonstrated in Figure 1a, the [ 18 F]PF-06455943 metabolism rate was moderate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations